Multi-criteria decision-making methods for project portfolio management: a literature review. (2018) - Danesh, Darius; Ryan, Michael J.; Abbasi, Alireza
Project portfolio management (PPM) has become a key element of large organisations' service delivery due to the close attention inherently paid to numerous issues in the discipline of project management. Its success is closely associated with the degree of understanding of its issues and the quality of decisions made at the portfolio level which can be addressed using multi-criteria decision-making (MCDM) methods. Although several of these MCDM methods have been introduced to support decision-making functions as part of PPM, there has been little assessment of their performances, particularly when combining some of them. This paper identifies the key challenges of PPM, proposes a new framework for classifying PPM MCDM related methods and presents a literature review of applications of MCDM methods to PPM.